Impact of the Liverpool Care Pathway on quality end‐of‐ care in residential care homes and home care-Nurses' perceptions - Cecilia Olsson; Elisabeth Kling; Karina Grundel Persson; Maria Larsson (Wiley, 2019)
Abstract Aim Aim was to describe how Registered Nurses (RNs) and assistant nurses (ANs) working in residential care homes and home care perceived quality end‐of‐life care after implementation of the Liverpool Care Pathway (LCP) in terms of subjective importance of care aspects and actual care given. Design Descriptive cross‐sectional. Methods Registered Nurses (N = 22; 100% response rate) and ANs (N = 120; 59% response rate) working in a Swedish municipality. Data collection with a study‐specific questionnaire (50 items) about perceived reality (PR) and subjective importance (SI). Non‐parametric statistics. Results Implementation of the LCP ensured systematic assessment and alleviation of patients' symptoms and needs. The ANs, more than the RNs, perceived that the patients received the best possible nursing and medical care (p = .01). Both groups considered that communication with patients and families as well as the information exchange between the team members was facilitated. Areas for improvement were identified about psychological and existential support and patients and families' participation in care.